2012
DOI: 10.1007/s00467-011-2072-x
|View full text |Cite
|
Sign up to set email alerts
|

Urine interleukin-18 and cystatin-C as biomarkers of acute kidney injury in critically ill neonates

Abstract: BackgroundUrinary interleukin-18 and cystatin-C are suggested to be biomarkers for predicting acute kidney injury (AKI). The aims of this study are to examine whether the urinary concentrations of interleukin-18 and cystatin-C vary with gestational age and other factors in non-AKI control neonates, and to determine whether urinary interleukin-18 and cystatin-C can predict AKI development in non-septic critically ill neonates, independently of potential confounders.MethodsWe enrolled 62 non-septic critically il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 41 publications
(59 reference statements)
1
54
1
8
Order By: Relevance
“…22 Moreover, this difference remained significant after adjustment for gestational Figure 1. Correlation between urinary angiotensinogen and gestational age or body weight.…”
Section: Comparison Of the Uagt Level In Neonates With Urinary Cysc-tmentioning
confidence: 89%
“…22 Moreover, this difference remained significant after adjustment for gestational Figure 1. Correlation between urinary angiotensinogen and gestational age or body weight.…”
Section: Comparison Of the Uagt Level In Neonates With Urinary Cysc-tmentioning
confidence: 89%
“…Different studies correlated renal functional status using pRIFLE criteria with renal biomarker (uCysC and uIL-18) 19,20 . As this biomarker are not widely available and costly, this study correlated renal impairment using pRIFLE criteria with Apgar score in asphyxiated neonate , so that renal impairment can be predicted early by low Apgar score in perinatal asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…18 In another study, a group of 62 critically ill neonates including eight term neonates with PA were recently evaluated for urinary biomarkers of AKI by Li et al 31 Urinary IL-18 was significantly higher in nonseptic critically ill neonates with AKI compared to controls. 31 Our study showed the presence of higher IL-18 levels in newborns with PA compared to controls. The sensitivity of uIL-18 was 93.3%; and the specificity was 90.5% in predicting AKI in newborns with PA.…”
Section: Discussionmentioning
confidence: 99%